2014
DOI: 10.1089/pho.2014.3821
|View full text |Cite
|
Sign up to set email alerts
|

The Fluence Effects of Low-Level Laser Therapy on Inflammation, Fibroblast-Like Synoviocytes, and Synovial Apoptosis in Rats with Adjuvant-Induced Arthritis

Abstract: Objective: The aim of this study was to evaluate the effect of low-level laser therapy (LLLT) operating at low and high fluences on joint inflammation, fibroblast-like synoviocytes (FLS), and synovial apoptosis in rats with adjuvant-induced arthritis. Background data: Rheumatoid arthritis (RA) is characterized by pronounced inflammation and FLS proliferation within affected joints. Certain data indicate that LLLT is effective in patients with inflammation caused by RA; however, the fluence effects of LLLT on s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
9
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 32 publications
2
9
0
2
Order By: Relevance
“…The immune cells, mast cells, may play a crucial role in mediating the establishment of networks among the circulatory, nervous and immune system at the acupoints [ 30 ]. Our results suggested after stimulation of the BL60 and KI3 in the AIA joint with laser, the TNF-α in the tibiotarsal joint reduced significantly, which is in accordance with our previous study[ 31 ]. This is probably because LA can promote local microcirculation to increase waste removal and adequate nutrient delivery to chondrocytes.…”
Section: Discussionsupporting
confidence: 93%
“…The immune cells, mast cells, may play a crucial role in mediating the establishment of networks among the circulatory, nervous and immune system at the acupoints [ 30 ]. Our results suggested after stimulation of the BL60 and KI3 in the AIA joint with laser, the TNF-α in the tibiotarsal joint reduced significantly, which is in accordance with our previous study[ 31 ]. This is probably because LA can promote local microcirculation to increase waste removal and adequate nutrient delivery to chondrocytes.…”
Section: Discussionsupporting
confidence: 93%
“…Hyperglycemia increases oxidative stress through various pathways . Hsieh et al found a significant decrease in MMP‐3 after irradiating Sprague‐Dawley rats using a 780‐nm GaAIAs laser with a fluence of 4.5 J/cm 2 , and concluded that PBM is beneficial in promoting healing by reducing inflammatory responses while altering expression of proteases in fibroblast‐like synoviocytes.…”
Section: Discussionmentioning
confidence: 99%
“…For a better understanding of concepts and effects, Table 1 presents PBM experimental studies [ 155 , 156 , 157 , 158 , 159 , 160 , 161 , 162 , 163 , 164 , 165 , 166 , 167 , 168 , 169 , 170 , 171 , 172 , 173 , 174 , 175 , 176 , 177 , 178 , 179 , 180 ].…”
Section: New Introspections and Perspectives On Photobiomodulationmentioning
confidence: 99%